New kid in school - Jones, Jasmine; Minsky, Terri Gould, Melissa Bargiel, Nina G. Bargiel, Jeremy J. (Disney Press : Volo New York, NY, 2003)
Lizzie is glad to have school lunch with her crush boy Ethan until she meets his new friend, a mysterious kid who just transferred from Fiji